The influence of formal institutions on the internationalization of companies in an emerging country - Marlon Monticelli, Jefferson; Vilasboas Calixto, Cyntia; Luís de Vasconcellos, Silvio; Lapuente Garrido, Ivan (Review of Business Management, 2017)
Purpose – The goal of this study is to use the institution-based view as the background for an investigation of how formal institutions influence the internationalization processes of firms from an emerging economy. Design/methodology/approach – Our case study is based on semistructured interviews with twenty-one representatives of formal institutions and firms in the Brazilian wine industry. Findings – It was noted that formal institutions have positive influences on the internationalization of Brazilian wineries by providing learning, relationship networks, intelligence about foreign markets, costs reduction, internationalization of business processes, and by promoting the home country’s image as a wine producer in foreign markets, and as a recognized supplier to the domestic market. They also have negative influences, as excessive bureaucracy, strikes, erection of legal barriers to trade with other countries, insufficient technical knowledge, high taxes, and favoritism benefiting the largest wine producers in the industry. Originality/value – The paper closes with suggestions for future research on how phenomena such as the relationship strategies established by the wineries impact upon internationalization and how decisions of a political nature made by formal institutions influence the wine industry, providing a new outlook on the internationalization of these firms.